Maxwell Fluid Performance on Free Convective Non-Newtonian Nanofluid Flow Over a Cone in Presence of Magnetic Field, Heat and Mass Transfer - Sathyanarayana, M.; Goud, T. Ramakrishna (Communications in Mathematics and Applications, 2023)
In this research work, the numerical technique called Runge-Kutta method along with shooting technique is used to find the numerical solutions in the presence of magnetic field, heat and mass transfer on steady, two-dimensional, viscous, incompressible, electrically conducting, Maxwell fluid flow towards a vertical cone with the effects of Thermophoresis and Brownian motion effects. For this investigation, the basic governing equations for this fluid flow were transformed into non-linear ODEs using the similarity quantities. Graphical visualizations of velocity, temperature, and concentration distributions are shown with the effects of various engineering parameters. Also, the numerical values of engineering quantities Skin-friction, Nusselt number and Sherwood number coefficients are presented in tabular forms. Finally, for program code validation, the present numerical results are compared with the published results available in literature. In this current work, the velocity profiles are decreasing with increasing values of Maxwell fluid and Magnetic field parameters. With the increasing effects of Brownian motion and thermophoresis the temperature profiles are increase. The concentration profiles are increasing with increasing values of thermophoresis parameter and reverse effect is observed in case of Brownian motion effect. Also, the concentration profiles are decreasing with rising values of Lewis number.
Keywords: Maxwell fluid; Nanofluid; Free convection; Magnetic field; Heat transfer; Mass transfer